(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Casual dining is more than just good food; it’s about the whole experience. This study set out to uncover what really matters to customers when they choose to dine in casual restaurants. Through firsthand feedback from regular diners in Dumaguete City, the research dug into the subtle details that often go unnoticed but make a big impact, like how fast the service is, how friendly the staff are, the feel of the place, and whether the experience feels worth the money spent. Rather than just measuring basic satisfaction, the study focused on what makes people enjoy their visit and want to come back. It looked closely at how things like ambiance, food quality, and even small personal touches shape the overall experience. The goal was to figure out what turns a simple meal into something memorable. The insights gathered from this study were used to build a practical guide, a framework, for restaurant owners and staff to better understand their customers and improve the way they deliver service. In the end, the study found that the real secret to success in casual dining isn’t just getting things right; it’s about creating moments that make people feel seen, valued, and glad they walked through the door.